MENINGKATKAN PEMAHAMAN KONSEP KELARUTAN DAN HASIL KALI KELARUTAN MELALUI PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE PADA SISWA KELAS XI SMA NEGERI 1 SUWAWA - Handayani, Tri; Ischak, Netty; Sihaloho, Mangara (Jurnal Entropi, 2009)
The research is classroom action research and conducted at students of XI class in SMA Negeri 1 Suwawa in 2008/2009 academics years. The sample was 26 students that consisted of 5 male students and 21 female students. The research aimed to improve students comprehension ability in solubility and solubility product concept through cooperative learning of Think-Pair-Share type. The research was had 2 cycles, in where there was an improving of teacher interaction in learning with average value as 3,27 (81,75%) in good category at first cycle and became 3,63 (90,75%) in excellent category at second cycle. In addition, there was an improving of students interaction with average value as 2,50 (62,5%) with enough criteria at first cycle and improved as 3,50 (80,75%) in excellent criteria at second cycle. Also, there was an improving of students achievement that was 62,5% at first cycle and improved to 88% at second cycle. Therefore, it showed that there was an improving of students comprehension ability in solubility and solubility product concept through Cooperative learning of Think-Pair-Share type. Hence, the hypothesis that stated, If in learning about solution and result times solution used cooperative learning of Think-Pair-Share type then students comprehension ability in XI class of SMA N 1 Suwawa can improve is accepted.